Vertical Distribution of Bacterial Community in Water Columns of Reservoirs With Different Trophic Conditions During Thermal Stratification - Yue, Yihong; Cai, Ling; Tang, Yi; Zhang, Yuanyuan; Yang, Ming; Wang, Fushun (Frontiers in Environmental Science, 2021)
Water eutrophication is a global ecological issue, and thermal stratification of water bodies can enable eutrophication. We examined bacterial communities in the stratified water columns and sediments in two different trophic reservoirs along the Wujiang River using quantitative real-time PCR and high-throughput sequencing. Bacterial 16S rRNA gene copies varied from 3.70×107 to 5.27×108 copies/L in the water column of Hongjiadu (HJD) Reservoir (60 m water depth) with slightly stratified variation; while in Wujiangdu (WJD) Reservoir (70 m water depth), bacterial abundance decreased markedly from the surface to the bottom(1.74×109 to 2.38×107 copies/L). The vertical distribution patterns of bacteria in both reservoirs resembled those of water Chlorophyll a concentrations. The abundance was negatively correlated with water depth, total nitrogen, nitrate, and positively correlated with water temperature and dissolved oxygen level. In contrast, the alpha diversity of bacteria showed the opposite trend in the vertical water column. Proteobacteria, Actinobacteria, and Bacteroidetes were the predominant phyla in the water column of both reservoirs. Compared to WJD Reservoir, HJD Reservoir displayed marked vertical spatial difference in bacterial community structure during thermal stratification. In particular, Pseudomonas was frequently detected at the bottom of the HJD Reservoir. These results were consistent with predictive metagenomic profiling that revealed different vertical functional variation patterns of the bacterial communities in the two reservoirs. The bacterial community structure of HJD Reservoir was associated with water D, ammonium, nitrite, and total phosphorus. The community structure of WJD Reservoir was related to water T, Chla, NO3--N, and TN. The findings highlighted the important roles played by thermal stratification and nutrients in shaping the water bacterial community structure. Additionally, the absolute abundance of water nitrifiers (AOB) and denitrifiers (narG, nirS, norB, nosZ) displayed significant vertical differences in the water columns of both reservoirs. Gene copies involved in denitrification were significantly higher than those involved in nitrification. Water phosphorus and nitrogen contents were important variables influencing the absolute abundance of ammonia oxidizers and denitrifying bacteria, respectively. Our study revealed that the emergence of thermal stratification was responsible for the vertical stratification of bacteria in water and affected the bacterial community structure together with nutrients.